Analisis Proses Pembelajaran IPS Melalui Media Whatsapp Di Sekolah Dasar - Silfa Fatmawati; Arsyi Rizqia Amalia; Iis Nurasiah (STKIP Andi Matappa Pangkep, 2020)
The purpose of this study was to describe and obtain information about the social studies learning process through WhatsApp media in grade 5 elementary schools. The research method uses descriptive qualitative because the aim is to analyze a problem that occurs. Qualitative research does not have the character of testing or rejecting a hypothesis, but tends to find new problems. In this study, it involved class 5 D homeroom teachers and 39 students of class 5 D at SDN Dewi Sartika CBM. The data collection technique uses primary data in the form of interviews and secondary data in the form of questionnaires and documentation in the form of photos and screenshot of social studies learning process carried out through WhatsApp media. The data analysis technique uses the stages of data reduction (data reduction), data presentation (data display) and drawing conclusions (conclusing drawing / verification). The result of this research is that learning conducted through WhatsApp is quite effective.